Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan, Dan Penghindaran Pajak Terhadap Manajemen Laba Dengan Leverage Sebagai Variabel Moderasi - Mahzum, Muhammad; Dzikri, Muhammad Afdhalu (Journal of Student Development Information System (JoSDIS), 2026)
This research aims to determine the effect of tax planning, deferred tax burden and Tax Avoidance with leverage as a moderating variable. The population used in this research is manufacturing companies with a sample of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) 2019 - 2023. The sampling technique used was purposive sampling and 20 food and beverage sub-sector companies were obtained as observations. as many as 100 observations. The analysis method used is moderated regression. Based on partial test results, tax planning and Tax Avoidance have no effect on earnings management. The deferred tax expense variable has a significant effect on earnings management. . Meanwhile, with the moderating variable, the partial test results show that tax planning, deferred tax burden, and Tax Avoidance do not have a significant effect on earnings management with leverage as a moderating variable found in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2019 - 2023.